The Prevalence of Uncorrected Refractive Errors in Primary School-Aged Children - Supriyanto, Ardi; Indrajanti, Mirza; Farfar, Inggrid Osya (Jurnal MedScientiae, 2025)
Refractive errors are one of the leading causes of visual impairment in children. If left uncorrected, these conditions can interfere with learning processes and overall child development. Objective: To determine the prevalence of uncorrected refractive errors among students at SDN 11 Pagi and SDN 17 Kebon Jeruk, West Jakarta, in 2025. Methods: This study employed a descriptive quantitative design with a cross-sectional approach. A total of 700 students who met the inclusion criteria were examined using a Snellen chart and a trial lens set. Results: The study found that 53.7% of students had uncorrected refractive errors. Astigmatism was the most common type, followed by compound myopic astigmatism and myopia. Conclusion: Refractive errors were more prevalent among female students (27.4%) compared to male students (26.3%), with the highest prevalence found in first and sixth-grade students. This study highlights the importance of early detection and routine vision screening among elementary school children to prevent long-term visual impairment.